Time analysis for the IAAF World Championships London 2017 10.000 m women's - Hanley, B.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
The women`s 10,000 m final took place on the evening on August 5th. In contrast to the close men`s final the night before, Ayana`s winning margin of over 46 seconds was the largest in World Championships history. The more intense battle was between Dibaba and Tirop for silver, with Nawawuna dropping off these two having been in contention with one lap remaining. Ayana, the World Record holder, was a minute slower than her time achieved in becoming 2016 Olympic Champion, but still recorded a World Leading time. The results for all finishers are shown. (Attention! registration on the IAAF site is required for downloading)